Factors associated with failure to correct the international normalised ratio following fresh frozen plasma administration among patients treated for warfarin-related major bleeding - Menzin, Joseph; White, Leigh Ann; Friedman, Mark; Nichols, Christine; Menzin, Jordan; Hoesche, Jan; Bergman, Garrett E.; Jones, Christopher (Thrombosis and Haemostasis, 2012)
This study assessed the frequency and factors associated with failure to correct international normalised ratio (INR) in patients administered fresh frozen plasma (FFP) for warfarin-related major bleeding. This retrospective database analysis used electronic health records from an integrated health system. Patients who received FFP between 01/01/2004 and 01/31/2010, and who met the following criteria were selected: major haemorrhage diagnosis the day before to the day after initial FFP administration; INR ≥2 on the day before or the day of FFP and another INR result available; warfarin prescription within 90 days. INR correction (defined as INR ≤1.3) was evaluated at the last available test up to one day following FFP. A total of 414 patients met selection criteria (mean age 75 years, 53% male, mean Charlson score 2.5). Patients presented with gastrointestinal bleeding (58%), intracranial haemorrhage (38%) and other bleed types (4%). The INR of 67% of patients remained uncorrected at the last available test up to one day following receipt of FFP. In logistic regression analysis, the INR of patients who were older, those with a Charlson score of 4 or greater, and those with non-ICH bleeds (odds ratio vs. intracranial bleeding 0.48; 95% confidence interval 0.31–0.76) were more likely to remain uncorrected within one day following FFP administration. In an alternative definition of correction, (INR ≤1.5), 39% of patients’ INRs remained uncorrected. For a substantial proportion of patients, the INRs remain inadequately or uncorrected following FFP administration, with estimates varying depending on the INR threshold used.
Keywords: International normalised ratio; warfarin; haemorrhage; fresh frozen plasma; emergency medicine